Frontiers in Guided Wave Optics and Optoelectronics - Bishnu Pal (IntechOpen, 2010)
As the editor, I feel extremely happy to present to the readers such a rich collection of chapters authored/co-authored by a large number of experts from around the world covering the broad field of guided wave optics and optoelectronics. Most of the chapters are state-of-the-art on respective topics or areas that are emerging. Several authors narrated technological challenges in a lucid manner, which was possible because of individual expertise of the authors in their own subject specialties. I have no doubt that this book will be useful to graduate students, teachers, researchers, and practicing engineers and technologists and that they would love to have it on their book shelves for ready reference at any time.
English
Keywords: Engineering; Physical Sciences; Engineering and Technology; Electrical and Electronic Engineering; Optical Engineering